Antibiotic-potentiating efficacy of Rosmarinus officinalis L. to combat planktonic cells, biofilms, and efflux pump activities of extensively drug-resistant Acinetobacter baumannii clinical strains - Khashei, Sanaz; Fazeli, Hossein; Rahimi, Fateh; Karbasizadeh, Vajihe (Frontiers in Pharmacology, 2025)
IntroductionThis research aimed to examine the action of commercial antibiotics against extensively drug-resistant (XDR) A. baumannii clinical strains when combined with Rosmarinus officinalis extracts.MethodsAgar well diffusion and broth microdilution were used to screen the antibacterial activity of crude ethanol extract and its fractions (hexane, intermediate, ethyl acetate, and water). The interactions between the extracts and antibiotics (gentamicin, tetracycline, cefepime, and ciprofloxacin) were evaluated by checkerboard assay. The anti-biofilm and efflux pump inhibition activities were determined by the microtiter plate method and dye accumulation assay using flow cytometry, respectively. The potential phytochemicals that contribute to the antibacterial effects of R. officinalis were identified using the liquid chromatography-mass spectrometry (LC–MS).ResultsR. officinalis crude extract (CE) demonstrated the best antibacterial activity with MIC values ranging from 300 to 600 μg/mL. The combination of CE and tetracycline exhibited the highest overall synergistic effect. This combination hindered biofilm formation ranging from 21.4% to 57.31% and caused a significant increase (up to 14%) in the fluorescence intensity in 75% of the studied strains. The LC-MS analysis of CE exhibited eleven compounds in which rosmarinic acid (55.53%) was the most abundant phenolic compound followed by cirsimaritin (11.46%), and p-coumaroyl hexoside acid (10.5%).DiscussionOverall, this is the first direct report that demonstrated the efficacy of R. officinalis when applied with conventional antibiotics on biofilm formation and efflux pump activity in XDR A. baumannii clinical strains.